INTEGRATION OF MAGNETIC RESIDUALS, DERIVATIVES AND LOCATED EULER DECONVOLUTION FOR STRUCTURAL AND GEOLOGIC MAPPING OF PARTS OF THE PRECAMBRIAN GNEISSES OF AGO-IWOYE, SOUTHWESTERN NIGERIA - ARIYO, Stephen; COKER, Joseph O.; ALAKA, Afolabi O.; ADENUGA, Omolara A.; BAYEWU, Olateju O. (GeoScience Engineering, 2020)
Ground based magnetic survey conducted between longitude 06O 55I 51IIN – 06O 55I 54IIN and latitude 03O 52I 06IIE – 03O 52I 4.8IIE (Olabisi Onabanjo University) remarkably revealed a consistent subsurface NW - SE structural azimuth of localized discontinuities within the shallowly buried heterogeneous basement rocks, which at exposed locations are composed of strongly foliated granite gneiss and migmatite-gneiss with veins and veinlets principally orientated in NNW – SSE direction. Magnetic survey of the area was preceded by site inspection to avoid metallic objects interferences. Field procedure in the area involved Cartesian gridding, base station establishment, data acquisition at gridded points, and repeated bihourly diurnal checks at the base station. At the processing stage, diurnal variation effect was aptly removed before subjection to Kriging (gridding). The gridded data was then prepared as input for Forward Fourier Filter Transform (FFT), which upon definition and implementation enabled Butterworth filtering of isolated ringing effects, reduction to the equator (RTE) for geomagnetic correction, and the use of Gaussian and Upward Continuation filtering for regional magnetic intensity trend determination. Removal of the regional magnetic intensity (RMI) from the total magnetic intensity (TMI) resulted in the derivation of the residual anomaly. Enhancement filters adopted for better resolution of the residual magnetic gradient include analytical signal (AS), tilt-angle derivative (TDR), vertical derivative deconvolution (VDD), and the first vertical derivatives (FVD). TMI and RMI values range between 32925nT – 33050nT and 32935nT – 333050nT respectively, while the residual gradient ranges between 15nT/m and 10nT/m; AS ranges between 0.28nT/m and 4.1nT/m; and TDR ranges from -1.4nT/m to 1.4nT/m. Source depth calculation estimated from power spectrum analysis and Euler deconvolution ranges between 1m and 15m. Composite overlay of magnetic maps revealed jointed and faulted zones within the area; exhibiting a NW-SE principal azimuth of Liberian orogenic impress, which are in consistence with the foliation direction of the jagged foliated bedrock with an estimated maximum overburden of about 15m. The structural significance of this area as a prospective hydro-geological centre, and as an undesirable spot for high-rise building has been accurately evaluated from research findings. Application of integrated geophysical approach, complemented by detailed geological studies may furnish greater information about the subsurface structural architecture. Keywords: Gneisses; Ground Magnetic Surveying; RTE; Structural discontinuities; TDR. DOI 10.35180/gse-2020-0027